Increasing the dielectric breakdown strength of poly(ethylene terephthalate) films using a coated polyaniline layer - Job, A. E.; Alves, Neri [UNESP]; Zanin, M.; Ueki, M. M. (Iop Publishing Ltd, 2003)
The dielectric strength of films made from poly(ethylene terephthalate) (PET) coated with a thin layer of polyaniline (PANI) was studied. The PANI layer was deposited on the PET films by the 'in situ' chemical polymerization method. The PANI layer of the PANI/PET films was undoped in NH4OH 0.1 M solution and re-doped with aqueous HCl solution under different pH values varying from 1 to 10. Electric breakdown measurements were performed by applying a voltage ramp and the results showed a dependence of the dielectric strength on the pH of the doping solution due to the changes in the electrical conductivity of the PANI layer. The dielectric strength of PET/PANI films treated under higher pH conditions showed an electric strength about 30% larger than the PET films, since it leads to a non-conductive PANI layer.